Development and Assessment of Screening Nomogram for Biliary Atresia Based on Hepatobiliary Ultrasonographic Features - Dai, Shu Yang; Sun, Yu Qi; Wu, Ying; Chen, Gong; Sun, Song; Dong, Rui; Zheng, Shan (Frontiers in Pediatrics, 2021)
Abstract Objectives: Biliary Atresia (BA) is a rare neonatal liver disease of which the early diagnosis remains a challenge for clinicians. Our center has established a nomogram diagnostic model based on clinical characteristics and liver function characteristics. We aim to develop and validate a nomogram that includes additional ultrasound found hepatobiliary abnormality with better BA early screening performance. Methods: In this single-center, retrospective cohort analysis, 1001 neonatal obstructive jaundice (NOJ) patients between 2012 and 2015 were enrolled. Multivariable analysis was used to identify clinical characteristics, laboratory liver function characteristics, and ultrasonic features that may early screen BA. A nomogram was developed to predict the probability of BA using multiple logistic regression analysis. This nomogram was subsequently validated using another cohort of 501 NOJ patients between 2015 and 2017. Calibration curve analysis and decision curve analyses were performed to evaluate and interpret the nomogram's clinical benefits. Results: Gender, direct bilirubin (DB), alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), fasting gallbladder visibility, fasting gallbladder filling, and common bile duct visibility were found profound statistical significance between the BA and non-BA groups (P < 0.05). The significant features were used to build the nomogram. The area under the receiver operating characteristic (ROC) curve (AUC) value of the novel nomogram (0.87) showed superior to the former nomogram (0.83) and GGT alone (0.81) in the prediction of BA. The calibration curve revealed a close resemblance between the predicted and the actual BA probabilities. Also, the net benefit from decision curve analysis (DCA) of the nomogram (0.54) was superior to the former nomogram (0.49) and GGT alone (0.45) at 80% of threshold possibility. Conclusions: The nomogram has demonstrated better performance for BA screening by including additional information of the US finding, holding a promising future as a non-invasive method for BA patients.